2023
DOI: 10.1021/acs.estlett.3c00394
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation and Mineralization of a Compostable Aromatic–Aliphatic Polyester during Industrial Composting

Abstract: Compostable plastics support the separate collection of organic waste. However, there are concerns that the fragments generated during disintegration might not fully biodegrade and leave persistent microplastic in compost. We spiked particles of an aromatic−aliphatic polyester containing polylactide into compost and then tracked disintegration under industrial composting conditions. We compared the yields against polyethylene. The validity of the extraction protocol and complementary microscopic methods (μ-Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…This indicates that CO 2 accounts for the majority of the total mass of the degradation products of compostable plastic composting. Other studies have also demonstrated this characteristic of compostable plastics . These experiments showed that certified compostable plastics that have gone through the AD biodegrade faster in the postdigestion composting step in comparison to certified compostable plastics that did not go through the AD process before composting.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that CO 2 accounts for the majority of the total mass of the degradation products of compostable plastic composting. Other studies have also demonstrated this characteristic of compostable plastics . These experiments showed that certified compostable plastics that have gone through the AD biodegrade faster in the postdigestion composting step in comparison to certified compostable plastics that did not go through the AD process before composting.…”
Section: Resultsmentioning
confidence: 99%
“… Fragment recovery tests using a biodegradable polymer powder : For method development, it was first checked, if any microplastic loss in the sediment would occur during centrifugation. For this purpose, we compared centrifugation with 1.6 g/cm 3 SPT solution to centrifugation with 1.8 g/cm 3 SPT solution and found 168 (1.6 g/cm 3 ) and 51 (1.8 g/cm 3 ) microplastic particles per gram LiHof C11 soil in the sediment using fluorescence microscopy for the analysis (the method description can be found in our previous study [1] ). The original spiking was 50 mg biodegradable fragments in 2 g of LiHof C11 soil, corresponding to about 4500–5000 particles by using the known size distribution and polymer density for calculation, assuming spherical particles.…”
Section: Methods Validationmentioning
confidence: 99%
“…To determine the microplastic recovery, the cryomilled polymer powder was added to 2 g of soil and intensively mixed into the soil by using a spatula. For real world samples it is recommended to use a mixing device (e.g., TurbulaSystem Schatz T2F [1] ) for homogenization and subsampling. Soil agglomerates are broken apart during the ultrasonication step.…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben qualifizierten Probennahmen und Probenvorbereitungen in Kombination mit mikroskopischen und spektroskopischen Methoden ist es auch notwendig, bestehende Standards anzupassen. [71][72][73][74] Die digitale Transformation hat das Potenzial, analytische Fragen, Arbeitsweisen und Labore grundlegend zu verändern. Labore haben…”
Section: Analytik In Der Chemischen Industrieunclassified